Performance Analysis of Machine Learning and Deep Learning Architectures on Early Stroke Detection Using Carotid Artery Ultrasound Images - S. Latha; P. Muthu; Khin Wee Lai; Azira Khalil; Samiappan Dhanalakshmi (Frontiers, 2024)
Indexed by WOS/Scopus/ERA